Estudo do comportamento de indicadores ambientais nos sistemas fluviais Madeira/Amazonas e Solimões/Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The Amazon basin, the largest watershed in the world, accounts for approximately 16% of the water discharged into the ocean and its broad scope results in greater sensitivity of its rivers to global climate change. The dynamic and availability of chemical elements in a system as complex rely on natural processes such as leaching of chemicals contained in the rocks as well as a source of anthropogenic activity. The objective of this study was to evaluate the spatial variation of physical and chemical parameters (temperature, turbidity, conductivity, total suspended solids, pH) and anion concentration (F-, Cl-, NO3-, NO2- and SO42-) in sections covering the main forming the Amazon: Solimões and Madeira river, in addition to characterize the bottom sediment of these systems in regard to its particle size, mineralogical composition (XRD) and concentration of the metals Fe, Mn, Zn, Cu, Cr, Ni and Pb (ICP-OES). With the exception of turbidity, both the parameters and the ions concentration presented their values below the maximum recommended by the CONAMA resolution 357/2005 for waters class 2. Both evaluated stretches showed medium and fine sand contents as the predominant composition in the bottom sediments, except for RMGua point Guayaramerín-BO, reflecting the higher concentration of metals in this sample. In bottom sediments there was a predominance of quartz, albite, clinochlore, illite, muscovite and microcline in the total fraction of these. The presence of heavy minerals such as andalusite, augite and rutile were viewed in the Solimões / Amazonas stretch where this occurrence may be associated with Içá and Solimões formations. The correlation analysis allowed to evaluate that metals such as Fe, Pb and Ni have high correlation with the mineralogical composition of the Solimões / Amazonas stretch. The high correlation between Zn and Fe with SO42- content indicates their relationship with pyrite deposits, though not rule out the influence of mining activities widespread in the region. In PCA analysis it was observed that the dispersion of data, both in the Solimões / Amazonas stretch and in Madeira / Amazonas, are caused by naturally occurring factors, despite the high incidence of human activities, mainly in the basin of Madeira.
Keywords: Bacia Amazônica; Hidroquímica; Caracterização sedimentar; Amazon basin; Hydrochemical; Sediment characterization; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA: QUÍMICA ANALÍTICA